2020
DOI: 10.1002/ajmg.a.62020
|View full text |Cite
|
Sign up to set email alerts
|

Coloboma may be a shared feature in a spectrum of disorders caused by mutations in the WDR37‐PACS1‐PACS2 axis

Abstract: We report a male adult with early infantile‐onset epilepsy, facial dysmorphism, and iridal and choroidal coloboma who had a de novo heterozygous mutation in PACS2, that is, c.625G > A p.(Glu209Lys). This specific mutation was previously reported in a patient with PACS2‐related disorder (early infantile epileptic encephalopathy 66). De novo heterozygous mutations in WDR37 have been shown to cause a novel human disorder, neurooculocardiogenitourinary syndrome (NOCGUS syndrome) (OMIM #618652), characterized by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Although there is not sufficient evidence to correlate these previously unreported findings with PACS2 , it would be reasonable to include brain MRI and echocardiography in the follow‐up of these patients. Seeing that the manifestation in two adult patients (Sakaguchi et al, 2021 and this work) is reminiscent of a connective tissue disorder, PACS2 should be considered in the differential diagnosis of patients with slender body build, particularly in the context of DEE. Further cases need to be identified to determine whether these particular findings are part of the evolving phenotype.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although there is not sufficient evidence to correlate these previously unreported findings with PACS2 , it would be reasonable to include brain MRI and echocardiography in the follow‐up of these patients. Seeing that the manifestation in two adult patients (Sakaguchi et al, 2021 and this work) is reminiscent of a connective tissue disorder, PACS2 should be considered in the differential diagnosis of patients with slender body build, particularly in the context of DEE. Further cases need to be identified to determine whether these particular findings are part of the evolving phenotype.…”
Section: Discussionmentioning
confidence: 83%
“…At least 21 unrelated individuals with PACS2 variants have been reported to date, all presenting a variable number of clinical features (Dentici et al, 2019; Mizuno et al, 2021; Olson et al, 2018; Sakaguchi et al, 2021; Sánchez‐Soler et al, 2021; Terrone et al, 2020). A compilation of the clinical findings in all these cases (including our patient, n = 22) mostly reveals developmental delay/intellectual disability of variable severity, early‐onset epilepsy, and cerebellar dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of whole-exome sequencing has resulted in the description of rare de novo mutations that are associated with diseased phenotypes or developmental syndromes. , This advancement has expanded our knowledge of protein networks by going beyond well-established signal transduction proteins and investigating poorly characterized proteins, such as the PACS-2 E209K variant that led to DEE66 in 28 individuals identified thus far. We determined that the E209K mutation prolongs the half-life of PACS-2 , leading to an enhanced interaction with 14-3-3ε and an increased susceptibility to apoptosis. These results further our understanding of PACS-2 and implicate various PACS-2:14-3-3 signaling pathways as critical molecular determinants of PACS-2 E209K mutation-related encephalopathies.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that at least 28 unrelated individuals displayed a heterozygous c. 625G>A (p. E209K, henceforth referred to as E209K) de novo missense mutation within the PACS-2 MR (Figure A). In addition, individuals harboring PACS-2 E209K polymorphism clinically present with postnatal epileptic seizures and various forms of cranial malformations . These symptoms associated with the E209K mutation were formally denoted as developmental and epileptic encephalopathy 66 (DEE66) by the NIH MedGen database .…”
Section: Introductionmentioning
confidence: 99%